2014
DOI: 10.4103/0972-2327.138475
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetic evaluation of ABCB1, Cyp2C9, Cyp2C19 and methylene tetrahydrofolate reductase polymorphisms in teratogenicity of anti-epileptic drugs in women with epilepsy

Abstract: Aim:Pregnancy in women with epilepsy (WWE) who are on anti-epileptic drugs (AEDs) has two- to three-fold increased risk of fetal malformations. AEDs are mostly metabolized by Cyp2C9, Cyp2C19 and Cyp3A4 and transported by ABCB1. Patients on AED therapy can have folate deficiency. We hypothesize that the polymorphisms in ABCB1, Cyp2C9, Cyp2C19 and methylene tetrahydrofolate reductase (MTHFR) might result in differential expression resulting in differential drug transport, drug metabolism and folate metabolism, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Another genetic variant investigated in the AED studies was the rs1805087 variant of MTR in children, which was associated with an increased risk of neurodevelopmental delay and fetal anticonvulsant syndrome in AED-exposed children (Dean et al, 2007 ). The maternal variants CYP2C19 * 2 and rs1202168 of ABCB1 , as well as the haplotype G/C/T (rs2214102/rs1202168/rs1128503) of ABCB1 , were also associated with an increased risk of congenital anomalies upon AED exposure (Jose et al, 2014 ). One study specifically examined the genetic susceptibility to phenytoin teratogenicity and found that a maternal haplotype of EPHX1 C/G (rs1051740/rs2234922) is associated with an increased risk of offspring craniofacial anomalies (Azzato et al, 2010 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another genetic variant investigated in the AED studies was the rs1805087 variant of MTR in children, which was associated with an increased risk of neurodevelopmental delay and fetal anticonvulsant syndrome in AED-exposed children (Dean et al, 2007 ). The maternal variants CYP2C19 * 2 and rs1202168 of ABCB1 , as well as the haplotype G/C/T (rs2214102/rs1202168/rs1128503) of ABCB1 , were also associated with an increased risk of congenital anomalies upon AED exposure (Jose et al, 2014 ). One study specifically examined the genetic susceptibility to phenytoin teratogenicity and found that a maternal haplotype of EPHX1 C/G (rs1051740/rs2234922) is associated with an increased risk of offspring craniofacial anomalies (Azzato et al, 2010 ).…”
Section: Resultsmentioning
confidence: 99%
“…The reviewed studies on AEDs mainly investigated MTHFR , which is associated with folate metabolism (Dean et al, 1999 , 2007 ; Kini et al, 2007 ; Jose et al, 2014 ). Folate is essential for both methylation and DNA synthesis, and folate metabolism is important for normal fetal development (Nazki et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…After treatment with anti-epileptic drugs (AEDs), most epileptic patients respond well to medications. However, about one-third of newly treated patients do not respond adequately to medications, because these patients exhibit drug resistance to AEDs [ 2 ]. P-glycoprotein (P-gp) was the first discovered human ABC (the ATP-binding cassette) transporter in drug-resistance ovarian cells several decades ago [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The reviewed studies on AEDs mainly investigated MTHFR, which is associated with folate metabolism (Dean et al, 1999(Dean et al, , 2007Kini et al, 2007;Jose et al, 2014). Folate is essential for both methylation and DNA synthesis, and folate metabolism is important for normal fetal development (Nazki et al, 2014).…”
Section: Discussion Key Findings and Methodological Limitationsmentioning
confidence: 99%
“…Another genetic variant investigated in the AED studies was the rs1805087 variant of MTR in children, which was associated with an increased risk of neurodevelopmental delay and fetal anticonvulsant syndrome in AED-exposed children (Dean et al, 2007). The maternal variants CYP2C19 * 2 and rs1202168 of ABCB1, as well as the haplotype G/C/T (rs2214102/rs1202168/rs1128503) of ABCB1, were also associated with an increased risk of congenital anomalies upon AED exposure (Jose et al, 2014). One study specifically examined the genetic susceptibility to phenytoin teratogenicity and found that a maternal haplotype of EPHX1 C/G (rs1051740/rs2234922) is associated with an increased risk of offspring craniofacial anomalies (Azzato et al, 2010).…”
Section: Perinatal Serotonergic Symptoms and Neurotransmitter Blood Concentrationsmentioning
confidence: 99%